High Temperatures During the Seed-Filling Period Decrease Seed Nitrogen Amount in Pea (Pisum sativum L.): Evidence for a Sink Limitation - Larmure, Annabelle; Munier-Jolain, Nathalie G. (Frontiers in Plant Science, 2019)
Higher temperatures induced by the on-going climate change are a major cause of yield reduction in legumes. Pea (Pisum sativum L.) is an important annual legume crop grown in temperate regions for its high seed nitrogen (N) concentration. In addition to yield, seed N amount at harvest is a crucial characteristic because pea seeds are a source of protein in animal and human nutrition. However, there is little knowledge on the impacts of high temperatures on plant N partitioning determining seed N amount. Therefore, this study investigates the response of seed dry matter and N fluxes at the whole-plant level (plant N uptake, partitioning in vegetative organs, remobilization, and accumulation in seeds) to a range of air temperature (from 18.4 to 33.2°C) during the seed-filling-period. As pea is a legume crop, plants relying on two different N nutrition pathways were grown in glasshouse: N2-fixing plants or NO3−-assimilating plants. Labeled nitrate (15NO3−) and intra-plant N budgets were used to quantify N fluxes. High temperatures decreased seed-filling duration (by 0.8 day per °C), seed dry-matter and N accumulation rates (respectively by 0.8 and 0.032 mg seed−1 day−1 per °C), and N remobilization from vegetative organs to seeds (by 0.053 mg seed−1 day−1 per °C). Plant N2-fixation decreased with temperatures, while plant NO3− assimilation increased. However, the additional plant N uptake in NO3−-assimilating plants was never allocated to seeds and a significant quantity of N was still available at maturity in vegetative organs, whatever the plant N nutrition pathway. Thus, we concluded that seed N accumulation under high temperatures is sink limited related to a shorter seed-filling duration and a reduced seed dry-matter accumulation rate. Consequently, sustaining seed sink demand and preserving photosynthetic capacity of stressed plants during the seed-filling period should be promising strategies to promote N allocation to seeds from vegetative parts and thus to maintain crop N production under exacerbated abiotic constraints in field due to the on-going climate change.